Anglo-Dutch War collection
Journal or daybook by an unknown scribe entitled "Journaal of Dag Register Van den beginne des tegenwoordige Oorlog tusseren de seven Vereenigde Provincien, en Engeland," (i.e. "Journal or daybook from the beginning of the present war between the Seven United Provinces and England") containing copies of correspondence, treaties, articles of agreement, declarations, admiralty lists, notes, commentary, poetry, and essays relating chiefly to the Fourth Anglo-Dutch War (1780-1784), the fall of the Dutch Republic, and trade and diplomatic relations between the Netherlands and the emerging United States.
Individuals represented in the journal include various Dutch officials, military officers, members of the court and nobility, and poets, John Adams, Samuel Huntington, Henry Laurens, John de Neufville, Hyde Parker, and John Rutledge.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
In Dutch.
Finding aid available in the Library of Congress Manuscript Reading Room.
Forms part of: Peter Force papers and collection (Series 8D : entry 31).
Keywords: Adams, John, -- 1735-1826.; Huntington, Samuel, -- 1731-1796.; Laurens, Henry, -- 1724-1792.; Neufville, John de; Parker, Hyde, -- 1714-1782.; Rutledge, John, -- 1739-1800.; Anglo-Dutch War, 1780-1784.; Dutch poetry; Great Britain -- History, Naval -- 18th century; Netherlands -- Commerce -- United States; Netherlands -- Foreign relations -- United States; Netherlands -- History, Naval; United States -- Commerce -- History -- 18th century; United States -- Commerce -- Netherlands; United States -- Foreign relations -- Netherlands